2010
DOI: 10.1002/pds.1963
|View full text |Cite
|
Sign up to set email alerts
|

The use of prescription medicines and self‐medication among children—a population‐based study in Finland

Abstract: Most of the children's medication consists of self-medication, and especially of vitamin use. However, also a considerable proportion had used prescription medicines, and a minority prescription medicines and self-medication concomitantly. In three of the cases, a combination of prescription and OTC medicine with a potential risk for interactions were found. Physicians should be aware of this wide use of self-medication when prescribing medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 36 publications
(72 reference statements)
4
51
0
3
Order By: Relevance
“…The final study sample was representative in age and gender of children less than 12 years old living in Finland [29]. The regional distribution of the children differed slightly from that of the target population: Southern region, 40.7% (the actual proportion of the children in that area is 41.1%); Western, 32.6% (34.9%); Eastern, 12.8% (9.9%); Oulu region, 10.1% (10.4%); Lapland, 3.4% (3.3%); and Å land 0.5% (0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The final study sample was representative in age and gender of children less than 12 years old living in Finland [29]. The regional distribution of the children differed slightly from that of the target population: Southern region, 40.7% (the actual proportion of the children in that area is 41.1%); Western, 32.6% (34.9%); Eastern, 12.8% (9.9%); Oulu region, 10.1% (10.4%); Lapland, 3.4% (3.3%); and Å land 0.5% (0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…1 In many highly developed countries, self-medication for children and adolescents in case of pain and other minor ailments has increased within the past decades. 5,6 The reasons for this development are still unclear. A recent US survey showed that in 1 week, twice as many children aged 0 to 11 years received OTC drugs as prescription medications.…”
mentioning
confidence: 99%
“…Students' perspectives on medicines and their use, was similar to that seen in previous studies in Finland [26,27,30]. Fourth graders' perspectives included the view that as well as the benefits, medication always includes risks such as the side effects.…”
Section: Discussionmentioning
confidence: 56%
“…In the initial discussions, students pondered that reliable information could be acquired from doctors, from a hospital and from a pharmacy, as has been found in previous studies [23,34,35,38,39]. Unlike previous studies [23,26,34,35,38] fourth graders did not point out the role of parents, teachers or patient inserts as being an information source. During the group discussions after intervention, they mentioned packages and labels, showing an understanding of the rational use of medicines.…”
Section: Discussionmentioning
confidence: 71%